ANALISA KERUSAKAN DAN PERBAIKAN HYDRAULIC LIFT CYLINDER PADA WHEEL LOADER KOMATSU WA180 - Sujahri, Irfan; Murhaban, Murhaban (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
PT. Beurata Subur Peusada is a factory engaged in the palm oil processing industry (PMKS). To produce quality and quality palm oil products, it must be supported by good production machines. Especially on heavy equipment that has a lot of problems, because it is influenced by the age of the machine which is more than 10 years old. The hydraulic lift cylinder serves to transport and lower the arm using oil fluid as the medium. This research is to identify the types, triggers, and identify steps to repair the Komatsu Wa 180 Hydraulic Lift Cylinder Wheel Loader. The checking method was tried visually on the Hydraulic Hose, control valve, working pump, and Hydraulic Cylinder. The purpose of this study is to analyze the trigger for the damage of the Hydraulic Lift Cylinder. Research obtained on the hydraulic lift cylinder, the occurrence of damage to the seal and pins which resulted in the performance of the Komatsu Wa 180 Wheel Loader being not optimal. In repairing it is tried by exchanging damaged components and sterilizing all components from dirt. Avoidance activities by carrying out daily checks and preventive maintenance methods.